Extent and characteristic of diversification among Hungarian agricultural holdings - Kissné Nagy , Csilla (Applied Studies in Agribusiness and Commerce, 2016)
Through the connection to rural resources agriculture has an impact on the three functions of countryside: ecology, society and economy. Resources of economy and production environment are continuously changing thus farmers have to adapt to these changing circumstances. One of the adaptation methods is the diversification of activities to promote effective capacity utilization and additional profit. However there is no standard definition of diversification from the point of agricultural economics aspect both traditional approaches and the influence of European Union should also be considered to define it. Diversification and alternative income opportunities could be subsistence possibilities for several farmers. This could be defined not only at private holdings’ but at enterprises’ level. According to a traditional approach Hungarian statistical databases collect on-farm and off-farm agricultural activities depending on the connection to resources of a farm business. Analysing this database an overall picture could be defined considering the position and characteristic of diversified farmers and the popularity of each activity among agricultural producers. Based on a study, published in 2011 (Hamza, 2011) this paper also involves the latest statistical data (2010, 2013). Analysing dataset of period 2000-2013 this paper gives an overall overview about national and regional position and characteristics of diversified holdings and activities. JEL code: Q19